Spices in the Middle Ages - Freedman, Paul H. (History compass, 2004)
Spices were highly prized in the Middle Ages for their culinary, medicinal and liturgical calue. They also had the attraction of exotic and mysterious origins. Their historical significance lies in their role as consumer items, their symbolic association with luxury but also with the sacred, and the stimulus the demand for spices gave to European voyages of exploration and colonization at the end of the Middle Ages.